The Effectiveness of Collaborative Writing Using Padlet on The Writing Skills of Senior High School Students - Sari, Intan Puspita (English Edu: Journal of English Teaching and Learning, 2024)
One of the most essential skills is writing. Writing functions as a medium for someone to express their thoughts and points of view, and it is an essential instrument for communication. Writing can not only be done individually but can also be done by more than one person to produce jointly written work, or what can be called collaborative writing. In today's learning, technology-based media is often used. One of the media that can be used for collaborative writing is Padlet. Padlet is an online site that facilitates teachers' and students' learning and is very suitable for collaborative learning, such as collaborative writing. This research used a quantitative approach with a quasi-experimental method with 33 students in class X-12 as the experimental class and 33 students in class X.10 as the control class at SMAN 1 Puri school, Mojokerto. Researchers used pre-test and post-test as data collection techniques to determine the effectiveness of collaborative writing using Padlet by increasing students' writing skills between before and after the treatment was given. In this study, researchers found an increase in post-test scores in the experimental class that received treatment using Padlet. Calculating the T-test for two sample variants with the same assumptions shows that the T count value of 1.997 is smaller than the T table, namely 2.631. This shows that collaborative writing using the Padlet website is effective for applying in learning writing.